Peran Persia Sebagai Pusat Global, Geopolitik dan Dakwah Serta Pemikiran dan Praktik Aliran Syi’ah - Al Musawa, Nabiel; Rasyid, Daud; Hidayat, Khairul; Farhana, Nurfitria; Rahman, Deni; Arafah, Mudrikatul; Santoso, Budi (LP2M Universitas Islam Ahmad Dahlan, 2024)
This article discusses the influence of Persia on the development of Shia Islam, particularly from a political perspective, focusing on the roles of the Safavid and Qajar dynasties. The Safavid Dynasty (1501–1736), founded by Ismail I, established the Imami sect as the state religion, uniting various tribes and ethnic groups in Persia and strengthening a national identity rooted in Shia Islam. The legacy of this dynasty is evident in its grand architectural achievements and literary contributions that enriched Persian culture. Subsequently, the Qajar Dynasty (late 18th to early 20th century) continued to play a strategic role in consolidating Shia Islam's position. Initiated by Agha Mohammed Khan Qajar, this dynasty unified Persia’s territories and elevated the role of religious scholars as key figures in society. This study employs a qualitative method with a literature review approach to analyze how these two dynasties institutionalized Shia Islam as the state religion and a cornerstone of national identity. Key findings reveal that the Safavid and Qajar dynasties played crucial roles in establishing Persia as the global center of Shia thought and practice, significantly impacting the geopolitical dynamics of the Islamic world. This influence solidified Persia’s position as a global hub for Shia Islam and reinforced its identity within the Islamic political landscape to the present day.